18F FDG PET-CT in oncology & interesting images - Ahmad Saad, Fathinul Fikri (Universiti Putra Malaysia Press, 2015)
The objective of this book is to facilitate medical registrar, radiologist and the potential inclined personnels in performing single PET-CT reading. About 70+ case vignette and their variations in the examination of cancer patients are presented as interesting illustrations with specific highlights on the basic principles of the examination techniques and the pittfalls. The author has given a particular scrutiny on the learning points each cases presented. There also revision quiz for formative assessment on the readers’ understanding of the entire subject matters. This book features a basic approach, equipping the beginning readers with essential skills to practice PET-CT reading and hence possessing a necessary ideas on the potential of the oncology cases using the hybrid molecular imaging technique.